Sociology of Islam: The Role of Muslim Communities in Addressing Contemporary Social Issues in Western Countries - Rahmat Ramdhani; Le Hoang Nam; Ari Supadi; Jasafat Jasafat (Journal of Noesantara Islamic Studies, 2025)
The role of Muslim communities in addressing contemporary social issues in Western countries has garnered increasing attention within the sociology of Islam. As these communities grow and diversify, their interactions with broader societal structures pose both challenges and opportunities for social cohesion. This study investigates the multifaceted contributions of Muslim communities in addressing social issues such as discrimination, inequality, and cultural integration in Western societies. The research aims to explore how these communities engage with civil society and policy frameworks to foster positive change and promote mutual understanding. Employing a qualitative methodology, the study integrates in-depth interviews, participant observations, and a review of secondary data from case studies in key Western countries. The findings reveal that Muslim communities play a significant role in advocating for social justice, challenging stereotypes, and building interfaith dialogue. These efforts are often mediated through community organizations, religious institutions, and grassroots initiatives, highlighting their agency in shaping inclusive societal norms. The study concludes that Muslim communities contribute to resolving social issues through adaptive strategies that balance Islamic principles with contemporary societal demands.